LA OCUPACIÓN INCA EN EL VALLE DEL CUNAS (JUNÍN, PERÚ): UNA APROXIMACIÓN DESDE EL SITIO ARQUEOLÓGICO DE ARHUATURO - Perales Munguía, Manuel F. (2004)
We describe a late prehispanic settlement called Arhuaturo which is located in the lower Cunas drainage in the southern part of the main Mantaro valley, in the central highlands of Peru. After a review of the relevant ethnohistorical information on the study area and the archaeological evidence from the site, we discuss its chronological position and the nature of the Late Intermediate Period and Late Horizon period occupations. We focus on the role of the settlement’s population, especially the elites, in the process of Inca conquest and the consolidation of the state power in the region.